2017
DOI: 10.1371/journal.pmed.1002223
|View full text |Cite
|
Sign up to set email alerts
|

Master Regulators of Oncogenic KRAS Response in Pancreatic Cancer: An Integrative Network Biology Analysis

Abstract: BackgroundKRAS is the most frequently mutated gene in pancreatic ductal adenocarcinoma (PDAC), but the mechanisms underlying the transcriptional response to oncogenic KRAS are still not fully understood. We aimed to uncover transcription factors that regulate the transcriptional response of oncogenic KRAS in pancreatic cancer and to understand their clinical relevance.Methods and FindingsWe applied a well-established network biology approach (master regulator analysis) to combine a transcriptional signature fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 39 publications
1
59
0
Order By: Relevance
“…Several recent studies have described the transcriptomic landscape of PDAC and identified different subtypes with different clinical outcomes and drug sensitivities . Table summarises several notable studies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several recent studies have described the transcriptomic landscape of PDAC and identified different subtypes with different clinical outcomes and drug sensitivities . Table summarises several notable studies.…”
Section: Introductionmentioning
confidence: 99%
“…This had identified three subtypes: classical, quasimesenchymal and exocrine‐like, which have different prognoses and different responses to treatment. This classification has subsequently been challenged and revised, with newer classifications being put forward . Moffitt et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Notch signaling has now long been found to be altered and pathophysiologically involved in pancreatic carcinogenesis. Various approaches to pharmacologically target oncogenic Notch signaling in different cancers including pancreatic cancer have been developed, including the application of γ-secretase inhibitors and antagonists against Notch ligands [73,74,75], and some of these endeavors are still underway at various stages of preclinical as well as early clinical evaluation [76,77,78,79,80,81,82]. …”
Section: Novel Therapeutic Targetsmentioning
confidence: 99%
“…The heterogeneity within tumor is thus a critical component of resistance mechanisms [21]. Technological progress and big data have led to a characterisation of pancreatic cancer's molecular identity (of mostly resected tumors) [22][23][24][25]. However, in contrast to other cancers such in lung cancer with EGFR mutations, these global approaches failed to identify simple therapeutic strategies based on a stratification of PDAC patients.…”
Section: Targeted Therapies In Pancreatic Cancer -What Can We Learn Fmentioning
confidence: 99%